Original paperComparison of safety and efficacy of paclitaxel-eluting stents with durable versus biodegradable polymer implanted in saphenous vein graft lesions. Nine-month angiographic and intravascular ultrasound follow-up - Pregowski, Jerzy; Witkowski, Adam; Chmielak, Zbigniew; Kalińczuk, Łukasz; Ciszewski, Andrzej; Karcz, Maciej; Przyłuski, Jakub; Jastrzebski, Jan; Wolny, Rafał; Dziarmaga, Mieczysław (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2012)
Aim : To compare safety and efficacy of stents eluting paclitaxel from biodegradable (Luc Chopin 2 stent) versus durable (Taxus Liberté stent) polymer implanted into saphenous vein grafts (SVGs). Material and methods: Consecutive patients with stable angina or non-ST elevation acute coronary syndrome with culprit de-novo lesions in SVGs were enrolled. The patients were randomized to treatment with Luc Chopin 2 or Taxus Liberté stents. The primary endpoint was neointimal hyperplasia volume measured with intravascular ultrasound performed 9 months after stent implantation. The secondary endpoint was late lumen loss assessed angiographically at 9-month follow-up. We randomized 26 patients to the Taxus Liberté group and 25 patients to the Luc Chopin 2 group. Results: During 9-month follow-up the frequency of cardiac death (0% vs. 8%, p = 0.5) and target lesion revascularization (20% vs. 4%; p = 0.2) was not significantly different in the Luc Chopin 2 and Taxus Liberté groups. We did not observe a significant difference in the neointima hyperplasia volume between Luc Chopin 2 and Taxus stents (15.8 ±14.5 mm3 vs. 11.9 ±29.4 mm3; p = 0.1). However, late lumen loss was larger in lesions treated with Luc Chopin 2 stents (0.59 ±0.74 mm vs. 0.30 ±0.81 mm; p = 0.015). Conclusions : Luc Chopin 2 stents eluting paclitaxel from biodegradable polylactic-co-glycolic polymer implanted into SVGs seem to be less effective in inhibition of neointimal proliferation assessed angiographically than durable polymer Taxus Liberté stents.